2023
DOI: 10.3390/app13148457
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tone and Stiffness of the Teres Major Muscle in Elite Handball Athletes: A Cross-Sectional Study

Abstract: Background: The aim of this study was to determine whether the elite handball (HB) athletes with glenohumeral internal rotation deficit (GIRD) present differences in the mechanical properties in the teres major muscle, and strength and extensibility of the posterior shoulder tissues of the throwing shoulder (TS) compared to the non-throwing (non-TS) and non-HB athletes. Methods: A cross-sectional study was carried out, with sixty male participants: 30 HB athletes with GIRD and 30 age-matched healthy non-HB ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A summary of the included trials is shown in Table 2 . Four of the six included trials were RCTs [ 16 , 17 , 23 , 56 ]. One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A summary of the included trials is shown in Table 2 . Four of the six included trials were RCTs [ 16 , 17 , 23 , 56 ]. One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six included trials were RCTs [ 16 , 17 , 23 , 56 ]. One study reported two sessions of DNY [ 57 ], two studies three sessions of DNY [ 16 , 56 ], and lastly, three studies only one session [ 17 , 22 , 23 ]. Four studies associated DNY with other treatments (manual therapy, strengthening exercises, diacutaneous fibrolysis (DF), stretching) [ 22 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barra-López et al suggested that this muscle promotes glenohumeral stability by resisting inferior displacement of the humeral head with the arm lifted [10]. The mechanical properties, like stiffness and tone, of this muscle have shown to be increased in TS compared to non-TS and non-handball athletes [11]. Therefore, the increase in the stiffness of the teres major muscle may reach the humeral head, favoring GIRD and reductions in tROM and HA.…”
Section: Introductionmentioning
confidence: 99%